Variable changes in body composition, strength and lower-body power during an international rugby sevens season - Mitchell, J. A.; Pumpa, K. L.; Williams, K. J.; Pyne, D. B. (The Journal of Strength and Conditioning Research, 2016)
This study determined whether body composition, strength, and power changes that occur during preseason can be maintained during an international rugby sevens season. Fourteen male international rugby sevens players (age 21.4 ± 2.2 years; mean ± SD) were categorized as forward (n = 7) or back (n = 7), and assessed for height, mass (M), skinfolds (S) (?7), upper-body (UB) strength, lower-body (LB) strength, and LB power. Bench press, back squat, and a countermovement jump were used to measure strength and power at 3 time points: initial, early season, and late season. Forwards were taller (185 ± 4 cm), heavier (95 ± 6 kg), and possessed a greater lean body mass (55.5 ± 4.0 M·S-0.14) than backs (181 ± 8 cm, 88.5 ± 5.5 kg, and 51.9 ± 3.4 M·S-0.14). Over the full season, small (~5 ± 5%; mean ± 90% confidence limits) positive changes occurred in body composition. Lower-body strength gained during the preseason, decayed in-season, whereas UB strength increased moderately (~10 ± 3%) across the season. Power showed inconsistencies between measured variables with a moderate positive change across the season in mean velocity and relative peak power. Forwards showed a small decrease in peak power (relative and absolute). Moderate changes were observed in mean power over the season, forwards decreasing (~6 ± 6%) and backs increasing (~8 ± 6%). Rugby sevens forwards in this study found it difficult to maintain and improve power qualities in-season. Training loads of forwards and backs should be differentiated to maximize strength and power in-season.